2004
DOI: 10.1299/jsmec.47.992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shear Stress on Permeability of Vascular Endothelial Monolayer Cocultured with Smooth Muscle Cells

Abstract: Effect of fluid shear stress on permeability of endothelial monolayer was investigated using an endothelial cell (EC)-smooth muscle cell (SMC) cocultured model (CM). Permeability of ECs to bovine serum albumin was measured after exposure to shear stress of 1.5 Pa for 48 hours. Morphology and VE-cadherin expression of ECs in CM was almost same as of ECs cultured alone (monocultured model, MM). Under static condition, EC permeability was 5.1 ± 3.0 × 10 −6 cm/sec (mean ± SD) in MM and 6.5 ± 3.4 × 10 −6 cm/sec in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 26 publications
(27 reference statements)
1
14
0
Order By: Relevance
“…SI is one for a circle and approaches zero for a line. Suciu (32), Chiu et al (4), and Sakamoto et al (27) used cell cultures to observe the cell alignment of endothelial cells as a response to shear stress. As shown in Fig.…”
Section: H911 Mass Transport Of Ldl With Effects Of Wall Shear Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…SI is one for a circle and approaches zero for a line. Suciu (32), Chiu et al (4), and Sakamoto et al (27) used cell cultures to observe the cell alignment of endothelial cells as a response to shear stress. As shown in Fig.…”
Section: H911 Mass Transport Of Ldl With Effects Of Wall Shear Stressmentioning
confidence: 99%
“…The effects of shear stress on endothelial cells have been investigated in various studies. Although there is no study that directly investigates the relationship between shear stress and the fraction of leaky junctions, there have been studies on the effect of shear stress on cell shape (4,17,27), proliferation rate (12, 41), and hydraulic conductivity and permeability (27,28). Levesque et al (17) observed a stenosed dog aorta and correlated the cell shape with levels of shear stress.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…exposed to low steady or highly oscillatory shear stress are roundly shaped and show a high-proliferation rate, leading to the formation of leaky junctions. When exposed to high steady shear stress, endothelial cells are elongated in the flow direction with a lower rate of mitosis and, hence, show a smaller number of leaky junctions compared with ones exposed to low steady or highly oscillatory shear stress (11,12,33,47,51). As a result, endothelial shear stress influences LDL transport into the artery wall by promoting or demoting the formation of leaky junctions, i.e., the primary LDL transport pathway.…”
Section: Acquisition and Processing Of Anatomy Datamentioning
confidence: 99%
“…Locally elevated concentrations of low-density lipoprotein (LDL) are considered to be the initiator of atherosclerotic plaque formation (37,46,48). Therefore, transport of LDL into arterial walls has been the subject of various experimental (8,11,35,39,47,48) and computational investigations (2,29,43,50,52,53,55,56,59).Computational LDL transport models, as recently reviewed by Khakpour and Vafai (28), are categorized into three types: wall-free models, homogenous wall models, and multilayer wall models. In the simple wall-free models, fluid dynamics and LDL transport are calculated solely in the artery lumen.…”
mentioning
confidence: 99%